The Pathogenetic Significance of Low Iodine Intake in Non-Endemic Goiter — Absolute Iodine Uptake - Harriet, Dige-Petersen (Nuklearmedizin - NuclearMedicine, 1977)
The blood inorganic iodine concentration (BII), the radioiodide clearance and the absolute iodine uptake (AIU) were determined in 27 patients with simple goiter and in 21 controls. The purpose was to evaluate the pathogenetic significance of low iodine intake for the formation of sporadic goiter. An early thyroid radioiodide clearance was measured by 132 I (5–30 min post injection), and the BII values were bases on the specific activity of I in saliva.The median BII levels of patients and controls were 1.1 and 1.5 μg/l respectively, and the urinary iodine excretion 67 and 79 M-g/day respectively, the difference was not significant. The radioiodide clearance was above the normal range in 13 out of 27 patients, and 16 of 27 patients had elevated or high normal AIU values. These patients included 7 out of 9 patients with diffuse, shortlasting goiter; the AIU of those with nodular goiter ranged from slightly subnormal to elevated. Only one exhibited a typical iodine deficiency pattern of very low BII, high radioiodide clearance and normal AIU.It is concluded that a simple causal relationship between low iodine intake and goiter formation could not be demonstrated.